RANCANGAN SISTEM PENGELOMPOKKAN BUAH BERDASARKAN KADAR VITAMIN MENGGUNAKAN METODE K-MEDOIDS - Sidik, Agung Purnomo; Hermansyah, Hermansyah; Aulia, Dina (Scenario (Seminar of Social Sciences Engineering and Humaniora); 2023, 2023)
Lau Gumba Village is a village located in Brastagi District, Karo Regency, North Sumatra Province which is quite well known because it has quite interesting tourist objects to visit. A village that presents the location of tourist attractions in the village displays a natural charm that is quite amazing for local and foreign tourists. Lau Gumba Village has many plantation locations for various types of fruit grown by village farmers, this is what makes the tourist attraction quite good and healthy for tourists. The village of Lau Gumba has fruit farming with a variety of good fruits, with the importance of paying attention to the quality and type of vitamins, because when people sell or consume fruit based on vitamin levels, it is very important to pay attention to the shape, freshness, color of the fruit consumed. However, this requires technology that can provide information on fruit grouping based on vitamin levels. As is the case with information that provides an explanation in the information in grouping fruit based on vitamin levels, it must include the correct data. The method used in this research is using UML (Unified Modeling Language), namely using the k-medoids method, web programming, mysql as data storage. With the application of information technology, it will have an impact on fruit grouping based on vitamin levels, so that farmers can easily classify harvested fruit based on the levels of vitamins produced.